2018
DOI: 10.1186/s12903-018-0595-2
|View full text |Cite
|
Sign up to set email alerts
|

Are the mutans streptococci still considered relevant to understanding the microbial etiology of dental caries?

Abstract: The mutans streptococci were once the primary focus of research dedicated to understanding the etiology of dental caries. That focus has now shifted to an emphasis on the ecological balances and complexities within the entirety of the plaque microbiome. Within that framework there are considerable differences of opinion regarding the importance and relative contributions of the mutans streptococci. This article explores the basis for the various viewpoints, the limitations of current knowledge, and the confoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 72 publications
(78 reference statements)
3
68
1
3
Order By: Relevance
“…However, due to the “Great Plate Count Anomaly”, the true complexity of the oral microbiota (and that of indeed every microbiota!) has only began to be realized following the relatively recent development of culture-independent detection methods, such as second-generation sequencing technologies (5, 9, 16, 50). Of these techniques, 16S sequencing has been the most widely utilized technique in characterizing microbial communities, including those of the oral cavity associated with dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, due to the “Great Plate Count Anomaly”, the true complexity of the oral microbiota (and that of indeed every microbiota!) has only began to be realized following the relatively recent development of culture-independent detection methods, such as second-generation sequencing technologies (5, 9, 16, 50). Of these techniques, 16S sequencing has been the most widely utilized technique in characterizing microbial communities, including those of the oral cavity associated with dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the canonical cariogenic species, S. mutans, was significantly associated with caries (3 rd most correlated species-level taxa according to supervised methods), but was found in relatively low abundances, and in only 11 of the 47 subjects. This indicates that S. mutans, when present, has a large influence on the pathogenicity of the oral microbiome due to its prodigious capacity to generate insoluble glucans and resultant biofilms (9, 26). Other oral microbiome studies have found S. mutans at low abundances (20, 21, 54), and the use of saliva in this study may explain its rarity, and possibly underestimation, here—as an exceptional biofilm-former, it is less likely to be shed from its dental plaque residence into the salivary milieu (55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Residents of the dental plaque have been implicated in a variety of diseases, including dental caries, which affects more than a third of the world’s population and results in approximately $300 billion in direct treatment costs to the global economy annually(15-17). Although caries is a polymicrobial disease caused by a dysbiosis in the dental plaque microbial community, Streptococcus mutans , with its copious acid production and prodigious biofilm formation, is still considered a primary etiologic agent(18, 19). To persist in the dental plaque community and cause disease, S. mutans must be able to outcompete commensal bacteria directly.…”
Section: Figurementioning
confidence: 99%